SINOPSIS DALAM PEMBELAJARAN SEJARAH (Cara Mudah Memahami dan Mengingat Peristiwa Sejarah) - Hairuddin Cikka (Scolae: Journal of Pedagogy, 2019)
History includes the journey of human life in filling the development of the world from time to time. Every history hasmeaning and value, so humans can make their own history and history shapes humans, using history as a living materialwill cause a variety of analyzes in the atmosphere of historical culture. History repeats itself again and again. Historyhas meaning and gives meaning where humans are like a world that revolves around itself. History is written as apicture or as a teacher who gives a guide. The Qur'an, among others, explains the stories as role models to be used as abasis for consideration for mankind in every action and attitude.In order to easily understand history learning, new breakthroughs need to be made so that students or anyone who readsor studies history are interested in learning history in order to understand and take advantage of every event that occurs,so the most effective solution is to make a synopsis in history courses or learning